Unveiling the Real Madrid effect: the impact of football-related acrimony on elections - Vincenzo Alfano; Salvatore Ercolano (Economia Politica, 2023)
Contributing to the literature on so-called irrelevant events, this article aims to investigate the existence of a relation between football results and voters' behaviour. There are indeed reasons to believe that football-related acrimony could influence electoral behaviour. More precisely, does the rank of a rival team and the distance between it and local teams influence the behaviour of the electorate? Spain seems to be the perfect case for study of this relationship, since the presence of football teams representing both local ( comunidad ) and central authorities (the Spanish Crown) allows us to study the effect of an important cleavage: the centre-periphery. This means that sport disputes may be reflected in voting preferences for ethno-regionalist parties. Following this reasoning, the better Real Madrid (the team representing the Crown) performs, and the closer the local team is to it (and thus actually competing), the stronger local supporters' sense of acrimony and desire for payback will be. By means of a quantitative approach, using data on election results and Spanish Liga rankings, our analysis confirms the existence of a negative correlation between Real Madrid's ranking and distance from local teams, and the share of votes in ethno-regionalist parties.
Keywords: D72; P48; 330; Football; Politics; Localism; Ethno-regionalism; Elections; Irrelevant events; Political conflict